2020
DOI: 10.1093/aesa/saaa004
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Abundance and Diversity of Fruit Flies (Diptera: Tephritidae) in Three Types of Plant Formations in Western Burkina Faso, West Africa

Abstract: Fruit flies are significant insect pests, worldwide. Tephritid species diversity and their seasonal abundance were investigated over 2 yr (May 2017 to May 2019) in Western Burkina Faso. A mass trapping experiment consisting of 288 Tephri Trap types, operating with four types of parapheromones comprising methyl eugenol, terpinyl acetate, trimedlure, and cue lure and an insecticide (Dichlorvos), was used for attracting and killing insects. Plant formations including natural fallows, mango orchards, and agrofores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 21 publications
2
17
0
8
Order By: Relevance
“…The very high proportions and prevalence of B. dorsalis in all the mango orchards in Togo is an evidence that this invasive species has settled in Togo and has undoubtedly constituted a threat to mango and other fruits production. (Bota et al 2018(Bota et al , 2020N'Da 2018;Zida et al 2020). The high proportion and prevalence of B. dorsalis in mango orchards do not seem to be explained solely by the effectiveness of the attractant used for this species but mainly by its very good adaptation to the agro-ecological conditions of the study area.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The very high proportions and prevalence of B. dorsalis in all the mango orchards in Togo is an evidence that this invasive species has settled in Togo and has undoubtedly constituted a threat to mango and other fruits production. (Bota et al 2018(Bota et al , 2020N'Da 2018;Zida et al 2020). The high proportion and prevalence of B. dorsalis in mango orchards do not seem to be explained solely by the effectiveness of the attractant used for this species but mainly by its very good adaptation to the agro-ecological conditions of the study area.…”
Section: Discussionmentioning
confidence: 79%
“…Those identified represent 77% Meyer 2005;De Meyer et al 2013). The flies identified up to species level were those of the Dacinae subfamily reported in Togo and other countries of the afrotropical region (Amevoin 2009;Ouédraogo et al 2011;Gomina et al 2012;De Meyer et al 2013;N'Da 2018;Zida et al 2020). The relatively high species richness obtained with a single study method applied over a month is an evidence that the species found in the mango orchards (which were at fruit ripening stage) and their surrounding vegetation, a favorable abiotic (temperature, relative humidity, precipitation, etc.)…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Assim, as espécies generalistas diferentemente das especialistas, apresentam maior distribuição por explorarem maior número de plantas hospedeiras (SELIVON, 2000;MINHIBO et al, 2019). A atração e ocupação de uma planta hospedeira por determinada espécie de mosca-das-frutas, não é um fator dependente apenas de um tipo de comportamento, mas sim de um conjunto hierárquico e dinâmico, ocasionado pela junção de múltiplos componentes distintos (ZIDA et al, 2020). As variações que remetem a utilização de plantas hospedeiras pelas espécies de Anastrepha, podem diferir dependendo do tipo de resposta às mudanças no seu estado fisiológico interno, por vezes relacionados à falta de hospedeiros preferenciais e aqueles vinculados a experiências anteriores (ALUJA; MANGAN, 2008).…”
Section: Plantas Hospedeirasunclassified
“…No Brasil são conhecidas 121 espécies de Anastrepha, com registros em praticamente todos os estados, sendo A. fraterculus e A. obliqua as espécies de maior importância e amplitude de distribuição (ZUCCHI;MORAES, 2008). As moscas-das-frutas constituem um dos grupos de maior importância econômica (ALUJA, 1999;ZIDA et al, 2020), fazendo-se necessário mais pesquisas com o intuito de entender os padrões de distribuição, abundância, biologia e comportamento, que servem de base para medidas de manejo de espécies-praga em ambientes cultivados.…”
Section: Introductionunclassified